Concepts, methods and applications of quantum systems in chemistry and physics : selected proceedings of QSCP-XXI (Vancouver, BC, Canada, July 2016) /: selected proceedings of QSCP-XXI (Vancouver, BC, Canada, July 2016). (2018) - Unknown
No abstract available